Effects of Noise and Serial Position on Free Recall of Spoken Words and Pupil Dilation during Encoding in Normal-Hearing Adults - Miseung Koo; Jihui Jeon; Hwayoung Moon; Myungwhan Suh; Junho Lee; Seungha Oh; Mookyun Park (Brain Sciences, 2021)
This preliminary study assessed the effects of noise and stimulus presentation order on recall of spoken words and recorded pupil sizes while normal-hearing listeners were trying to encode a series of words for a subsequent recall task. In three listening conditions (stationary noise in Experiment 1; quiet versus four-talker babble in Experiment 2), participants were assigned to remember as many words as possible to recall them in any order after each list of seven sentences. In the two noise conditions, lists of sentences fixed at 65 dB SPL were presented at an easily audible level via a loudspeaker. Reading span (RS) scores were used as a grouping variable, based on a median split. The primacy effect was present apart from the noise interference, and the high-RS group significantly outperformed the low-RS group at free recall measured in the quiet and four-talker babble noise conditions. RS scores were positively correlated with free-recall scores. In both quiet and four-talker babble noise conditions, sentence baselines after correction to the initial stimulus baseline increased significantly with increasing memory load. Larger sentence baselines but smaller peak pupil dilations seemed to be associated with noise interruption. The analysis method of pupil dilation used in this study is likely to provide a more thorough understanding of how listeners respond to a later recall task in comparison with previously used methods. Further studies are needed to confirm the applicability of our method in people with impaired hearing using multiple repetitions to estimate the allocation of relevant cognitive resources.